Multiple Triggering Factors Of Generalized Pustular Psoriasis: A Case Report - Utami, Mugi Restiana; Yuniaswan , Anggun Putri (Ahmad Dahlan Medical Journal, 2025)
Generalized Pustular Psoriasis (GPP) is a rare, severe systemic inflammatory disorder driven by dysregulation of the interleukin-36 (IL-36) pathway. Flares are often precipitated by multiple triggering factors, including infections, medication and underlying comorbidities. A 40-year-old overweight male with a history of pustular psoriasis and poor treatment adherence presented with a severe flare of widespread, painful pustules. The presentation was complicated by consumption of diclofenac and multiple infections, including cellulitis and untreated dental caries, which progressed to septic shock and acute kidney injury (AKI). He was managed with intravenous antibiotics and systemic immunomodulators (cyclosporine, then methotrexate), leading to significant clinical improvement. Host factors like obesity and non-adherence created a pro-inflammatory state, while acute infections and non-steroidal anti-inflammatory drugs (NSAID) acted as potent triggers for IL-36 upregulation, igniting a severe inflammatory cascade. This convergence led to life-threatening systemic complications, underscoring the complexity of the disease. Severe GPP flares are often triggered by a convergence of overweight status, NSAID and acute infections. Effective management requires a holistic, multidisciplinary approach that aggressively identifies and treats all contributing triggers to improve outcomes.